Efeito antichagásico de peptídeos derivados da hemocianina do camarão Penaeus monodon - Monteiro, Marília Lopes (2019)
Chagas disease, caused by Trypanosoma cruzi, is responsible for the infection of millions of people in about 21 countries, responsible for the highest number of deaths among parasitic diseases. Although it has major social and economic impacts in Brazil, the only drug used for treatment is benzonidazole, which has limited efficacy and high toxicity. The aim of the present work is to investigate the antihagasic activity of hemicyanin-derived fragments of Penaeus monodon shrimp with antimicrobial potential (Hmc666-678, Hmc364-382, Hmc185-197 and Hmc476-498), as well as to investigate their selectivity and mechanism of action. Cytotoxicity of the peptides was evaluated in LLC-MK2 cells by the MTT method. A cytotoxic effect was observed from the 50μM concentration. Subsequently, the effect of the peptides on the epimastigote forms was investigated at 24, 48 and 72 hours by counting in a Neubauer chamber, finding for Hmc666-678 IC50 / 24h = 4.01μM; IC50 / 48h = 4.86 μM; IC50 / 72h = 8.83 μM, for Hmc364-382 IC50 / 24h = 4.79μM; IC50 / 48h = 4.5 μM; IC50 / 72h = 11.27 μM, for Hmc185-197 IC50 / 24h = 34.14μM; IC50 / 48h = 86.06 μM; IC50 / 72h = 90.86 μM and for Hmc476-498 IC50 / 24h = 24.22 μM; IC50 / 48h = 25.63 μM; IC50 / 72h = 22.13 μM. In trypomastigotes the effect was evaluated at the time of 24 hours by counting in Neubauer chamber, where Hmc666-678, Hmc364-382 have inhibitory effect at almost all concentrations tested in a similar manner. It was estimated the selectivity index (IS), where the peptide Hmc364-382 has lS above 55.24, Hmc666-678 has lS above 45.35, Hmc476-498 has lS 1.99 and Hmc185-197 lS of 1.27. Based on the selectivity index the Hmc666-678, Hmc364-382 were selected for the later trials. Effect against amastigote forms was also found after 24 hours of incubation for both peptides at the IC 50, IC50 / 2 and 2xIC50 concentrations and no reduction in the percentage of infected cells was observed. In the search for the mechanism of action of the selected peptides the ultrastructural changes were analyzed by scanning electron microscopy (SEM) after 24 hours of incubation and transmission (TEM) after 12 incubation. Effects on plasma membrane integrity (7-aminoactinomycin D labeling), externalization of phosphatidylserine (AX labeling), reactive oxygen species (oxidized 2'-7'-dichlorofluorescein labeling) and mitochondrial transmembrane potential rhodamine 123) were evaluated by flow cytometry. The results of MET indicate autophagic signs, whereas SEM and cytometry indicate necrosis and late apoptosis. Suggesting an autophagic onset and progression to apoptosis and necrosis. The results were expressed as mean ± SEM and analyzed using ANOVA with Bonferroni's post-test in the program GraphPad Prism 5. In conclusion, the four evaluated peptides showed anti-hagasic potential and Hmc666-678, Hmc364-382 present promising effect, with effect on all the evolutionary forms of T. cruzi and IS above 45 with involvement of necrosis, autophagy and apoptosis in its mechanism of action